2015
DOI: 10.1186/s40623-015-0203-5
|View full text |Cite
|
Sign up to set email alerts
|

Harmonics of whistler-mode waves near the Moon

Abstract: Harmonic spectral features of electromagnetic waves in the frequencies of several Hz around the Moon have been identified by Kaguya. The waves have steepened waveforms peculiarly in the compressional component. The fundamental waves have almost the same properties as narrowband whistler-mode waves with the frequencies near 1 Hz, which have been observed around the Moon. The waves are observed around the terminator region in the solar wind near the lunar magnetic anomalies at the altitudes under 120 km. We sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…One‐hertz waves are whistler mode waves, which have frequencies near 1 Hz as measured in a spacecraft frame, and these waves are observed frequently in planetary upstream regions. These low‐frequency upstream whistler waves have been observed at Mercury (Fairfield & Behannon, ; Le et al, ; Orlowski et al, , ; Russell, ), Venus (Orlowski et al, ; Orlowski & Russell, ; Orlowski et al, ; Russell, ), Earth (Balikhin et al, ; Fairfield, ; Greenstadt et al, ; Heppner et al, ; Holzer et al, ; Hoppe et al, , ; Orlowski et al, , ; Russell et al, ; Russell & Farris, ; Russell, ; Tsurutani et al, ), Mars (Brain et al, ), Saturn (Orlowski et al, , ; Russell, ; Sulaiman et al, ), Jupiter (Tsurutani et al, ), Uranus (Smith et al, , ), the Moon (Halekas et al, , ; Nakagawa et al, , ; Tsugawa et al, , , , ), and at interplanetary shocks (Ramírez Vélez et al, ; Wilson et al, ). The frequency of these waves monotonically decreases for planets that are farther away from the Sun.…”
Section: Introductionmentioning
confidence: 95%
“…One‐hertz waves are whistler mode waves, which have frequencies near 1 Hz as measured in a spacecraft frame, and these waves are observed frequently in planetary upstream regions. These low‐frequency upstream whistler waves have been observed at Mercury (Fairfield & Behannon, ; Le et al, ; Orlowski et al, , ; Russell, ), Venus (Orlowski et al, ; Orlowski & Russell, ; Orlowski et al, ; Russell, ), Earth (Balikhin et al, ; Fairfield, ; Greenstadt et al, ; Heppner et al, ; Holzer et al, ; Hoppe et al, , ; Orlowski et al, , ; Russell et al, ; Russell & Farris, ; Russell, ; Tsurutani et al, ), Mars (Brain et al, ), Saturn (Orlowski et al, , ; Russell, ; Sulaiman et al, ), Jupiter (Tsurutani et al, ), Uranus (Smith et al, , ), the Moon (Halekas et al, , ; Nakagawa et al, , ; Tsugawa et al, , , , ), and at interplanetary shocks (Ramírez Vélez et al, ; Wilson et al, ). The frequency of these waves monotonically decreases for planets that are farther away from the Sun.…”
Section: Introductionmentioning
confidence: 95%
“…13,34 It predicts that multiple reflected whistlers gradually refract away from the Earth. Such predictions cannot be made for whistler modes in lunar crustal magnetic fields 35 or for low frequency whistlers at the bowshock 36 or near reconnection regions. 37,38 Nonuniform magnetic fields also exist in the exhaust region of helicon thrusters 14,16,39 or toroidal plasma devices [39][40][41][42] with the focus on plasma production rather than wave refraction.…”
Section: Introductionmentioning
confidence: 97%
“…Their analysis suggested that broadband and narrow band waves are different views of the same waves propagating in the solar wind frame. In addition, the harmonics of the whistler waves have also been observed around lunar magnetic anomalies near the terminator region of Moon from Kaguya (Tsugawa et al 2015).…”
Section: Discussionmentioning
confidence: 94%
“…The abundance of positive charge in the range 10 −5 to 10 −7 cm −3 can accelerate electrons up to 1 keV and broadband electrostatic noise due to the counterstreaming electron beams has been found as a result of this process. Electrostatic solitary waves and whistler waves have been observed around Moon (Halekas et al 2006;Tsugawa et al 2011Tsugawa et al , 2012Tsugawa et al , 2015Nakagawa et al 2011). Electrostatic solitary waves has been observed on the day-side lunar surface as well as at the boundary of the lunar wake from Kaguya (Hashimoto et al 2010).…”
Section: Discussionmentioning
confidence: 98%